Communication strategies in the online teaching learning process during pandemic Covid-19 - Isnawijayani Isnawijayani; Rahma Santhi Zinaida; Genoveva Refina Virgi Handianita; Tri Widayatsih; Siti Rahayu; Dwi Muhammad Taqwa (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
Communication in education sector carried out by teachers and student, The main requirements are creation and communication of an effective learning and communicators in delivering learning material. Since December 2019, during the Covid-19 Pandemic, it is necessary to apply appropriate communication strategies in delivering learning materials. This study aims to reveal the Communication Strategy in Online Teaching Learning Process During Pandemic Covid-19. The subject was student and teacher in 6 th grade Xaverius 4 Palembang Elementary school. This research used descriptive qualitative research, data collection techniques used observation by reviewing online teaching and learning activities, interviews with 6 teachers as key informant and data analysis using data reduction, data display, and conclusion drawing/verification. As the result, the Teacher Communication Strategy that was produced in an Effort to Improve Student Learning Process at SD Xaverius 4 Palembang During the Covid-19 Pandemic period using online communication media and social media, Zoom and Whatsapp.